2021
DOI: 10.3390/molecules26030578
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl Cellulose Entrapped in a Poly(vinyl) Alcohol Network: Plant-Based Scaffolds for Cartilage Tissue Engineering

Abstract: Cartilage has a limited inherent healing capacity after injury, due to a lack of direct blood supply and low cell density. Tissue engineering in conjunction with biomaterials holds promise for generating cartilage substitutes that withstand stress in joints. A major challenge of tissue substitution is creating a functional framework to support cartilage tissue formation. Polyvinyl alcohol (PVA) was crosslinked with glutaraldehyde (GA), by varying the mole ratios of GA/PVA in the presence of different amounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Recently, Qi et al (2018) [304] demonstrated an effective in vivo bone regeneration in a mouse calvarial defect model and in vitro osteoblast differentiation of human mesenchymal stromal cells by using a non-woven CMC sheet (loaded with calcium phosphate). Most recently, Namkaew et al (2021) [308] reported a polyvinyl alcohol-based scaffold material for supporting cartilage formations at post-surgical conditions. The incorporation of CMC with this porous scaffold material improved the physical and swelling properties that made it more suitable for this purpose.…”
Section: Bone-tissue Engineeringmentioning
confidence: 99%
“…Recently, Qi et al (2018) [304] demonstrated an effective in vivo bone regeneration in a mouse calvarial defect model and in vitro osteoblast differentiation of human mesenchymal stromal cells by using a non-woven CMC sheet (loaded with calcium phosphate). Most recently, Namkaew et al (2021) [308] reported a polyvinyl alcohol-based scaffold material for supporting cartilage formations at post-surgical conditions. The incorporation of CMC with this porous scaffold material improved the physical and swelling properties that made it more suitable for this purpose.…”
Section: Bone-tissue Engineeringmentioning
confidence: 99%
“…In addition, it has good biocompatibility with the human body, low toxicity, high surface area, resistance and rheological properties while being a renewable material. Thus, in the recent years, cellulose has experienced an increasing interest in the tissue-engineering and regenerative-medicine fields, with applications in skin [ 21 ], bone [ 22 ], nerves [ 23 ], blood vessels [ 24 ] and cartilage [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…DAC can be successfully prepared from cellulose or methylcellulose by using sodium periodate oxidation process and possess well biodegradation and biocompatibility properties. Recently, a scaffold prepared by entrapped carboxymethyl cellulose in a poly(vinyl) alcohol network has been introduced, but the scaffold needed further glutaraldehyde crosslinked process [ 33 ]. Researchers also tried to use an electrospinning technique to prepare a hyaluronic acid/poly (3-hydroxybutyrate)/chitosan/carbon nanotubes scaffold for cartilage repair, the scaffold has enough tensile strength, and the hydrophilic ability of the scaffold could be enhanced by the increase in hyaluronic acid concentration [ 17 ].…”
Section: Discussionmentioning
confidence: 99%